Canada's Jews : in time, space and spirit - Robinson, Ira, 1951- (Jews in space and time., 2013)
Canada is home to one of the world's largest and most culturally creative Jewish communities, one of the few in the Diaspora that continues to grow demographically. With its ability to mirror trends found in Jewish communities elsewhere (particularly the United States) while simultaneously functioning as a distinct society, Canada's Jewish community holds great interest for scholars, exercising a measurable influence on the culture and politics of World Jewry. Consisting of a series of essays written by experts in their respective fields, Canada's Jews is a topical encyclopaedia, covering a wide variety of topics, from history and religion to the intellectual and cultural contributions of Canada's Jews. An indispensable reference book for both laypeople and for scholars of Jewish and Canadian studies.